Variation in carbon isotope composition of plants across an aridity gradient on the Loess Plateau, China - Yanzheng Yang; Ruikun Gou; Jun Zhao; Ning Qi; Zhongming Wen; Jalal Kassout; Ruonan Li; Guanghui Lin; Hua Zheng (Global Ecology and Conservation, 2022)
Carbon isotope composition (indicated by leaf δ13C) reflects plants' strategies to balance carbon acquisition and water loss, which is directly linked to water use efficiency. At a large scale, leaf δ13C has been demonstrated to be closely related to climate and plant functional types; however, at a regional scale, its variation across an aridity gradient and species categories and its covariation with traits in leaf economic spectrum (LES) traits are still unclear. Here, a multivariate statistical analysis was carried out with 271 observations of leaf δ13C from 22 sampling sites on the Loess Plateau. Our results showed that (1) mean leaf δ13C did not differ significantly among life forms in C3 plants, with the maximum mean values occurring in geophytes (−26.31‰) and the minimum values occurring in lianas (−28.29‰); (2) the leaf δ13C responses of different life forms, families and species categories to climates were consistent for C3 plants, namely, they presented similar response rates to changes along the aridity gradient (represented by the moisture index); (3) climate, soil, species category, and leaf economic spectrum traits jointly explained 78.4% of the variation in leaf δ13C for C3 plants. Species category was the largest determinant of leaf δ13C variations for both C3 and C4 plants. Revealing the variation in leaf δ13C of the Loess Plateau plants not only helps us to understand plant adaptation strategies under arid conditions but also provides scientific support for ecological management in vegetation restoration regions.